Asymmetric Total Syntheses of (–)-Dihydromaritidine and (–)-Oxomaritidine - Yadav, Abhinay; Majumder, Satyajit; Das, Mrinal Kanti; Mondal, Ayan; Bisai, Alakesh (Synlett, 2022)
A concise catalytic asymmetric approach to naturally occurring Amaryllidaceae alkaloids sharing a 5,10b-ethanophenanthridine skeleton [(–)-oxomaritidine, (–)-dihydromaritidine, (–)-maritidine, and (–)-epi-maritidine] has been envisioned. The key intermediate in this strategy was obtained by a Pd(0)-catalyzed decarboxylative allylation of a 2-arylcyclohexan-1-one-derived allylenol carbonate (87%, 96% ee).
Keywords: Amaryllidaceae alkaloids; asymmetric total synthesis; oxomaritidine; dihydromaritidine; maritidine; epi-maritidine